Evaluation of a three-way crossbred chicken developed for rural poultry under farm and backyard conditions for growth and production traits - RAJKUMAR, U; HAUNSHI, S; PASWAN, C; REDDY, B L N; YADAV, S P (The Indian Journal of Animal Sciences, 2018)
The growth and production performance of a promising three way cross was evaluated under farm and backyard conditions to assess its suitability as backyard chicken variety. The data generated on 200 birds from backyard and 136 birds from farm conditions was analyzed to study the effect of sex on growth and rearing system on growth and production traits. Sex had significant influence on body weights from 6 to 16 weeks of age. Sexual dimorphism was clearly observed in three-way cross with significantly higher body weights in cocks than hens under both farm and backyard conditions. The body weight of male and female birds at 16 weeks of age was 1704.12±16.89 and 1308.22±15.11 g, under farm conditions, while it was 1504.44±32.33 and 962.45±28.22 g, respectively in backyard conditions. Sex had significant effect on the shank length at all ages with longer shanks in males. The laying period body weights were significantly higher in farm reared birds. The type of rearing system significantly influenced age at sexual maturity (ASM), egg weight and egg production till 52 weeks of age. The egg production at 40 and 52 weeks of age was significantly lower in scavenging birds grown in backyard conditions. The ASM was 144.55±1.38 and 198.32±12.23 days in farm and backyard conditions, respectively. The egg production at 52 weeks of age was 146.33±4.41 and 118.40±8.11 eggs in farm and backyard conditions, respectively. The annual egg production (72 weeks of age) was 227.81±6.75 eggs in farm. The study concluded that the better performance of this three-way cross under farm and backyard system with respect to growth and egg production makes it a promising egg type variety for rural poultry farming in the country.